Answer :

Given:

taking LCM


using (a - b)2 = a2 + b2 - 2ab



8x2 - 8x + 4 = 17x2 - 17x cross multiplying


9x2 - 9x - 4 = 0


Using the splitting middle term - the middle term of the general equation is divided in two such values that:


Product = a.c


For the given equation a = 9 b = - 9 c = - 4


= 9. - 4 = - 36


And either of their sum or difference = b


= - 9


Thus the two terms are - 12 and 3


Sum = - 12 + 3 = - 9


Product = - 12.3 = - 36


9x2 - 9x - 4 = 0


9x2 - 12x + 3x - 4 = 0


3x(3x - 4) + 1(3x - 4) = 0


(3x - 4) (3x + 1) = 0


(3x - 4) = 0 or (3x + 1) = 0



Hence the roots of equation are


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

If the roots of tMathematics - Board Papers

Find the roots ofRD Sharma - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics